Teknologi Tepat Guna E-Goverment Kotim Untuk Pembagian Dana Plasma Perkebunan Kelapa Sawit Studi Kasus Desa Sumber Makmur Kecamatan Telawang Berbasis Web - Novita Sari; Depi Rusda (STMIK Budi Darma, 2020)
Plasma is the empowerment of land as simple as the community, plasma coconut plantation is an area of ??plasma developed by the nucleus company with plantation crops. In the early days of integrating large plantations with smallholder plantations (smallholders), the term used was Nurleus Estate Smallholder (NES), the term later changed to Inti Rakyat Perkebunan (PIR) company. The information system for plasma oil palm plantations is smallholder plantations, which in development are integrated into large private plantations. The state (PBSN) and large state plantations (PBN), because the skills of farmers are not smart, while the funds are funded by the government through banking in the form of credit. Oil palm plantations play an important role in the Indonesian economy and become the basis of life for some people. In the early stages of operationalization, the plasma oil palm plantations ran smoothly where each party was involved. The method in developing this system is by using DSDM (Dynamic System Development Method)